Sport and Oral Health : A Concise Guide - Budd, Siobhan C.; Egea, Jean-Christophe (Springer International Publishing : Imprint: Springer, 2017)
TThis book aims to explore the intricate interrelationship between oral health and sport, with the focus on highly popular team games, endurance sports, and explosive events. In order to understand the vulnerability of athletes of all levels of ability to oral health problems, relevant aspects of sports physiology and training are outlined, as are the predisposing behavioral, psychological, and physiological elements. Specific sports-related oral risk factors are identified and detailed, and the dental conditions frequently observed in athletes are explained. The dental clinical reality of athletes reveals a wide spectrum of oral consequences, affecting both soft and hard tissues, that can adversely impact on training and competitiveness. Principles of dental management are highlighted, and therapeutic solutions provided for the most common dental lesions. Emphasis is placed on preventative measures and solutions adapted to the athlete's individual needs, as well as the importance of effective collaboration with a diverse team of professionals. The book will be of interest to dentists, health professionals, sports coaches, athletes, and teachers and students of dentistry and medical disciplines.